Exploring the Capabilities of the Fourth Industrial Revolution for Improved Public Service Delivery in Nigeria - TEMITOPE, Ojogiwa Oluwaseun; JOHN, Sokfa F.; QWABE, Bongani Reginald (PT Keberlanjutan Strategis Indonesia, 2023)
The modern evolution of the Fourth Industrial Revolution (4IR) comes with new trends in technology that are altering the customary way of undertaking government tasks. The alterations appear in the form of both opportunities and threats, based on the strengths and weaknesses of extant practices and systems operating in the Nigerian public sector. Therefore, the government is faced with the challenge of coping with new demands and some unanticipated risks in incorporating and adapting to the 4IR. Although the 4IR is considered valuable, the extent of its influence on Nigerian service delivery and how to harness its worth has not been established. This article seeks to determine the existing level of the public sector’s service delivery in relation to innovation and technological advancements. It further investigates how the 4IR can influence and harness improvement in the delivery of public services in Nigeria. A review of secondary sources from reports, government documents and extant scholarly literature was undertaken and data were analysed thematically. While the Nigerian government has made some effort to provide the public sector with innovative technology, it is essential to improve on this provision to maximise the opportunities and strengths of the 4IR. Therefore, this article recommends the intensification of technological and digitalisation capabilities by providing suitable human and financial capital, necessary to improve service delivery, particularly in Nigeria.